2022
DOI: 10.1186/s13023-022-02337-2
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations from the IRDiRC Working Group on methodologies to assess the impact of diagnoses and therapies on rare disease patients

Abstract: Rare disease patients face many challenges including diagnostic delay, misdiagnosis and lack of therapies. However, early access to diagnosis and therapies can modify the management and the progression of diseases, which in return positively impacts patients, families and health care systems. The International Rare Diseases Research Consortium set up the multi-stakeholder Working Group on developing methodologies to assess the impact of diagnoses and therapies on rare disease patients. Using the patients’ jour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 12 publications
(10 reference statements)
0
24
0
Order By: Relevance
“…Using a mother-child cohort that links children to mothers’ genetic carrier screening status, we have identified that PheIndex Scores are lower at one or two years of follow-up in children whose mothers received CS-L relative to CS-S. We believe that our PheIndex algorithm will address an unmet need to identify children with rare genetic disorders and potentially help overcome well-known obstacles such as underdiagnosis and delayed diagnosis. 20…”
Section: Discussionmentioning
confidence: 99%
“…Using a mother-child cohort that links children to mothers’ genetic carrier screening status, we have identified that PheIndex Scores are lower at one or two years of follow-up in children whose mothers received CS-L relative to CS-S. We believe that our PheIndex algorithm will address an unmet need to identify children with rare genetic disorders and potentially help overcome well-known obstacles such as underdiagnosis and delayed diagnosis. 20…”
Section: Discussionmentioning
confidence: 99%
“…The International Rare Disease Research Consortium (IRDiRC) roadmap 2017-2027 challenged the community with three goals, of which Goal 1: All patients coming to medical attention with a suspected rare disease will be diagnosed within one year if their disorder is known in the medical literature; all currently undiagnosable individuals will enter a globally coordinated diagnostic and research pipeline 3 . These "currently undiagnosable individuals" are de ned in this project as those having undergone an inconclusive WES.…”
Section: Discussionmentioning
confidence: 99%
“…Data from January 2021 show that 4,480 out of 6,171 RD 2 are genetic RD (72,5%), and 1,588 of them (35%) do not yet have a clearly identi ed causative gene. 3 Rare diseases are characterised by the di culty in obtaining a correct and timely diagnosis, because of their rarity, scarcity of patients and inequalities in access to expertise. 4 During their diagnostic journey, patients can receive a clinical diagnosis 5 (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…One of the vexing challenges in rare diseases is that we are only halfway towards the declared goal of granting every patient with a rare disease their right to an accurate molecular diagnosis within a year of presentation 23,24 . The fact that the diagnostic odyssey continues unabated even after whole-genome sequencing suggests that new approaches need to be implemented and the use of LRS represents one such approach.…”
Section: Discussionmentioning
confidence: 99%